EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH MATERI PERTIDAKSAMAAN KUADRAT PADA SISWA KELAS X MA - Wisnu Siwi Satiti; Dita Ayu Perdani (Universitas KH. A. Wahab Hasbullah, 2019)
This research is aimed to measure the effectivity of Problem Based Learning models and it’s application to the learning process. The subject of this research is the student of X MIPA 7 Madrasah Aliyah Negeri 3 Jombang that contains 46 students. Meanwhile, the object of this research is mathematics learning process using Problem Based Learning models. This research was done using the experimental method and One-Shot Case Study design. The application of One-Shot Case Study is giving a treatment to the subject of the research. The kind of data that was being collected in this research is quantitative data. The data then, being analysed using paired sample t-test. The analysis was done using SPSS program and shown the value of Sig.calculate (0.000) < α (0.05) which means Ha is accepted and H0 is rejected. So, there is differences between pretest result anf postest result. Therefore, it can be concluded that problem based learning models is effective for mathematics learning in grade 10th MA.